Reorganization of intra-ASEAN trade flows: the China factor - Devadason, E.S. (2009)
There is burgeoning literature on the implications of China's ascendance on the region . There are claims that China's influence on ASEAN (Association of Southeast Asian Nations) is direct in that she has encouraged more exports to flow into her huge markets and changed trade flows amongst member countries. Demand and supply are deemed to have become more China-centered. The study therefore examines the dynamic shifts in trade between the five original ASEAN member countries to identify if China has indeed reorganized trade flows away from intra-A SEAN interactions to that of individual ASEAN countries with China. Specifically, the study explores the plausibility of China as a ' factor' that influences(directl y/ indirectly) bilateral intra-ASEAN trade flows through demand (exporting country)and supply (importing country). China's integration in the region increases the size of the key ASEAN member economies export market (scale of production). There is also no indication that import sourcing from China by ASEAN countries reduces export expansion within the latter. The results accord with the fact that though China has become an important export destination and an import source for individual ASEAN countries, this has not reduced intra-ASEAN trade.